Evaluation of Reported Adverse Drug Reactions in Antibiotic Usage: A Retrospective Study From a Tertiary Care Hospital, Malaysia - Arulappen, Ann L.; Danial, Monica; Sulaiman, Syed A. S. (Frontiers in Pharmacology, 2018)
Adverse Drug Reaction (ADR) primarily caused by many drugs including antibiotics. At present, the incidence and pattern of ADR caused by antibiotics have remained as neglected area in Malaysia. This study was conducted to determine the incidence and analyse the pattern of ADR caused by antibiotics among patients in a tertiary care hospital. It is a 2 year retrospective observational study conducted at Hospital Pulau Pinang, Malaysia. All eligible patients who had antibiotic prescribed belonging to any age group either from outpatient or inpatient that had experienced ADR was included in this study. The outcomes were measured with the aid of Naranjo’s and Hartwig’s scales. The incidence of the adverse drug reactions among patients prescribed with antibiotics in Hospital Pulau Pinang is about 1.1%. Vancomycin and Trimethoprim/ Sulfamethoxazole both are considered to be the major contributors to ADR incidences. The skin was the most affected organ by adverse drug reactions followed by gastrointestinal system. Most of the severe adverse drug reactions were caused by Penicillin. The causality relationship of all the severe reactions was mostly probable. General Medicine unit had reported the highest number of adverse drug reactions caused by antibiotics. The common manifestations of adverse drug reactions are acute kidney injury and exanthem. In addition, majority of the adverse drug reactions caused by antibiotics were reversible. A large multicentre study is suggested to confirm the present findings.